Apparent survival rates of adult Lesser Spotted Eagle Clanga pomarina estimated by GPS-tracking, colour rings and wing-tags. Issue 1 (2nd January 2017) - Väli, Ülo; Bergmanis, Uģis
ABSTRACT: Capsule: In the migratory Lesser Spotted Eagle Clanga pomarina, colour rings and Global Positioning System transmitters indicated annual survival rates similar to other large raptors, but the rate suggested by wing-tags was significantly lower due to the higher rate of tag loss.